Barriers to Education and Shared Decision Making in the Chronic Kidney Disease Population: A Narrative Review. Issue 1 (November 2018) - Cassidy, Brendan P.; Getchell, Leah E.; Harwood, Lori; Hemmett, Juliya; Moist, Louise M.
Purpose of review: Provision of education to inform decision making for renal replacement therapy (RRT) is a key component in the management of chronic kidney disease (CKD), yet patients report suboptimal satisfaction with the process of selecting a dialysis modality. Our purpose is to review the influencers of RRT decision making in the CKD population, which will better inform the process of shared decision making between clinicians and patients. Sources of information: PubMed and Google Scholar. Methods: A narrative review was performed using the main terms "chronic kidney disease, " "CKD, " "dialysis, " "review, " "decision-making, " "decision aids, " "education, " and "barriers." Only articles in English were accessed. The existing literature was critically analyzed from a theoretical and contextual perspective and thematic analysis was performed. Key findings: Eight common themes were identified as influencers for decision making. "Patient-focused" themes including social influence, values and beliefs, comprehension, autonomy and sociodemographics, and "clinician-focused" themes including screening, communication, and engagement. Early predialysis education and decision aids can effectively improve decision making. Patient-valued outcomes need to be more fully integrated into clinical guidelines. Limitations: This is not a systematic review; therefore, no formal tool was utilized to evaluate the rigor and quality of studies included and findings may not be generalizable. Implications: Standardized comprehensive RRT education programs through multidisciplinary health teams can help optimize CKD patient education and shared decision making. Involving patients in the research process itself and implementing patient values and preferences into clinical guidelines can help to achieve a patient-centered model of care.